Cartografia do saneamento básico do Rio Grande do Norte - Lucas Costa Rodrigues; Joselito da Silveira Junior; Izabela Cristiane de Lima Silva; Aldo Dantas (Confins)
The objective of this article is to present a summary of the situation of basic sanitation in Rio Grande do Norte State, based on the spatial mapping of certain variables that characterize the state from the institutional point of view, the norms and infrastructures of sanitation services, presenting the current situation of water supply, sanitary sewage, management and management of solid waste and urban drainage and management of rainwater in the State. The article also discusses the importance of the elaboration and implementation of Municipal Plans of Basic Sanitation, fundamental instrument of municipal management and that has in federal law 11.445 / 2007 its legal basis. This study is part of the "Profile survey and municipal socioeconomic diagnosis" aiming at the improvement and technical specialization of human resources in municipal sanitation plans that originates in a Decentralized Execution Term (TED) between FUNASA and UFRN. This has resulted in a cartography of the main analyzed variables and a graphic modeling that seeks to symbolize important aspects for a representation and discussion of basic sanitation in the state, choosing the fundamental structures.